2017
DOI: 10.1186/s40169-016-0133-2
|View full text |Cite
|
Sign up to set email alerts
|

The antineoplastic drug, trastuzumab, dysregulates metabolism in iPSC‐derived cardiomyocytes

Abstract: BackgroundThe targeted ERBB2 therapy, trastuzumab, has had a tremendous impact on management of patients with HER2+ breast cancer, leading to development and increased use of further HER2 targeted therapies. The major clinical side effect is cardiotoxicity but the mechanism is largely unknown. On the basis that gene expression is known to be altered in multiple models of heart failure, we examined differential gene expression of iPSC‐derived cardiomyocytes treated at day 11 with the ERBB2 targeted monoclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 54 publications
6
37
0
Order By: Relevance
“…Lapatinib is also known to cause widespread dysregulation of cholesterol biosynthetic enzymes (Necela et al, 2017), as observed here for hiPSC-CMs. We also find that many cell cycle genes are downregulated when hiPSC-CMs are exposed to TKIs.…”
Section: Discussionsupporting
confidence: 60%
“…Lapatinib is also known to cause widespread dysregulation of cholesterol biosynthetic enzymes (Necela et al, 2017), as observed here for hiPSC-CMs. We also find that many cell cycle genes are downregulated when hiPSC-CMs are exposed to TKIs.…”
Section: Discussionsupporting
confidence: 60%
“…Compared with animal models, hiPSC‐CMs are more representative of human cardiac physiology in terms of ion channel expression, heart rate, and myofilament composition . Several studies exploring the cardiotoxicity of different chemotherapy agents using stem cell models have been described in the past few years (summarized in Table ).…”
Section: Modeling Anticancer Therapy Mediated Cardiotoxicity In Vitromentioning
confidence: 99%
“…A recent study demonstrated that trastuzumab induces cardiotoxicity in hiPSC‐CMs that was dependent on the activation of the erythroblastic oncogene B2/B4 (ErbB2/B4) by either neuregulin (NRG‐1) or heparin‐binding epidermal growth factor, suggesting that trastuzumab is blocking the cardioprotective effects of the ErbB2/4 pathway . In contrast, two other studies showed that trastuzumab‐mediated cardiotoxicity on hiPSC‐CMs is independent of the ErbB2/B4 pathway activation , highlighting the need to develop standardized cell culture conditions to improve the validity of hiPSC‐CMs in trastuzumab‐toxicity screening. More recently, the potential cardiotoxic effects of pertuzumab and trastuzumab‐emtansine (TDM1), a novel antibody–drug conjugate targeting the ErbB2 receptor were tested in the hiPSC‐CMs .…”
Section: Modeling Anticancer Therapy Mediated Cardiotoxicity In Vitromentioning
confidence: 99%
“…It also inhibits HER2 shedding and metalloproteinase activity by decrease PTEN phosphorylation or AKT de‐phosphorylation to induce tumour cells death . Cardiotoxicity is a major reported side effect in trastuzumab‐treated patients and in some cases led to stop the antibody administration …”
Section: Anit‐her2 Mabs and Derivativesmentioning
confidence: 99%
“…[79] Cardiotoxicity is a major reported side effect in trastuzumab-treated patients and in some cases led to stop the antibody administration. [82,83] Pertuzumab (PERJETA)…”
Section: Trastuzumab (Herceptin)mentioning
confidence: 99%